2014
DOI: 10.1073/pnas.1402353111
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of diverse pathogens in human cells by synthetic microRNA-like oligonucleotides inferred from RNAi screens

Abstract: Systematic genetic perturbation screening in human cells remains technically challenging. Typically, large libraries of chemically synthesized siRNA oligonucleotides are used, each designed to degrade a specific cellular mRNA via the RNA interference (RNAi) mechanism. Here, we report on data from three genome-wide siRNA screens, conducted to uncover host factors required for infection of human cells by two bacterial and one viral pathogen. We find that the majority of phenotypic effects of siRNAs are unrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…When siRNA screens have been performed in different laboratories to identify host factors against a virus, the genes in published hit lists have shown poor overlap, suggesting serious inherent problems in the approach. This is in part explained by different screening procedures and analysis, as well as by siRNA off-target effects (31)(32)(33). When our analysis was limited to the 13,000 transcribed genes, the number of candidates was reduced to about 70% of the original lists independently of the Qiagen or Dharmacon screens.…”
Section: Resultsmentioning
confidence: 99%
“…When siRNA screens have been performed in different laboratories to identify host factors against a virus, the genes in published hit lists have shown poor overlap, suggesting serious inherent problems in the approach. This is in part explained by different screening procedures and analysis, as well as by siRNA off-target effects (31)(32)(33). When our analysis was limited to the 13,000 transcribed genes, the number of candidates was reduced to about 70% of the original lists independently of the Qiagen or Dharmacon screens.…”
Section: Resultsmentioning
confidence: 99%
“…False-positive results can be found in siRNA screens due to off-target binding of siRNAs. Off-target siRNA binding is most likely to occur in the 3= untranslated region (3= UTR) of mRNA (24,25), where siRNAs exhibit microRNA-like properties upon binding of a limited number of bases, akin to a microRNA seed region, to mRNA (24)(25)(26). Indeed, it has been proposed that the data returned from some screens are the result of unintentional screening of partial seed sequence matches and not on-target binding of siRNA (26).…”
Section: Development Of a High-throughput Screening Methodologymentioning
confidence: 99%
“…Off-target siRNA binding is most likely to occur in the 3= untranslated region (3= UTR) of mRNA (24,25), where siRNAs exhibit microRNA-like properties upon binding of a limited number of bases, akin to a microRNA seed region, to mRNA (24)(25)(26). Indeed, it has been proposed that the data returned from some screens are the result of unintentional screening of partial seed sequence matches and not on-target binding of siRNA (26). Therefore, using genome-wide enrichment of seed sequence (GESS) matches (17,18), we investigated if the siRNAs screened in this study (all 4 siRNAs that constitute the pools of siRNAs used) were enriched with seed sequences that could bind either human 3= UTRs or full human mRNA transcripts.…”
Section: Development Of a High-throughput Screening Methodologymentioning
confidence: 99%
“…Furthermore, comparing the performance of AS/RND4 with that of siRND4 revealed that the former is ∼16-fold more potent, consistent with their presumed siRNA-like and miRNA-like mechanisms, respectively. In a post-analysis of three genome-wide siRNA screens conducted to uncover genes involved in bacterial/viral infections (Franceschini et al 2014), investigators concluded that the majority of the phenotypic effects were not derived from the full siRNA sequence but rather from the siRNA seed regions. To assess the effects of an rnd-siRNA with randomized positions in the seed on a whole-transcriptome scale, we transfected HeLa cells with siRND2 at 40 nM and purified total RNA 72 h post-transfection.…”
Section: Position Of Randomized Sites Influences the Silencing Propermentioning
confidence: 99%
“…In addition to Ago2-mediated sequence-dependent OTEs, additional sequence-dependent OTEs can derive from RISC activation of the passenger strand (Clark et al 2008), immunostimulation (Sledz et al 2003;Hornung et al 2005;Judge et al 2005), and RISC-mediated silencing of mRNAs in a microRNA (miRNA)-like fashion (Doench et al 2003;Saxena et al 2003;Birmingham et al 2006;Jackson et al 2006;Aleman et al 2007;Vickers et al 2009;Shin et al 2010;Marine et al 2012). Indeed, a recent study declared that most of the phenotypic effects in three independent genome-wide siRNA screens stemmed from miRNA-like OTEs rather than from on-target silencing (Franceschini et al 2014). Sequence-independent OTEs are also known and derive from saturation of RNAi machinery components (Jackson and Linsley 2010) and cell toxicity leading to cell death/growth inhibition.…”
Section: Introductionmentioning
confidence: 99%